National Economy Recovery by Crowdfunding Policy as Alternative in MSME Financing - Rudolf Haiti; Lu Sudirman (Widya Yuridika, 2022)
The covid-19 pandemic has been affecting MSME actors significantly. One of the problems faced by MSME actors due to this pandemic, is difficulty in collecting business capital. Therefore, the Indonesian Government presents crowdfunding as a solution. The crowdfunding itself intends to strengthen MSME financially and encounter investors and MSME actors in one platform. Crowdfunding collects funds from the community and is managed by a crowdfunding provider institution. In this case, information technology-based crowdfunding is one of the MSME capital solutions during the COVID19 pandemic. This information technology-based crowdfunding provides alternative capital for MSMEs other than conventional banks and financing institutions, sourced from public funds (crowd funds). This study aims to provide an overview of how crowdfunding can be alternative funding in Indonesia and overcome MSME capital difficulties based on capital market laws and OJK regulations (The Indonesian Financial Services Authority). This legal research uses doctrinal research methods to analyze whether this crowdfunding policy can be an opportunity for economic recovery in Indonesia. The results of this study indicate that crowdfunding can be a funding solution in Indonesia and an alternative in economic recovery after the COVID-19 pandemic based on regulations issued by OJK in POJK (the Indonesian Financial Services Authority Regulation) Number 57 of 2020.